Gas Leak Localization Using Mobile Sensor Networks - Bambang Tutuko; Siti Nurmaini; Agus Triadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
A swarm robotics localization strategybased on deliberates fuzzy and swarm behavior isproposed in this paper. Localization is the processof determining the positions of robots or targetsin whole swarms environment. To localize thetarget in real environment, experiment isconducted utilize three identical robots withdifferent color as mobile sensor node. Fuzzy logicand swarm behavior are keeping the swarmrobots position and direction with a certaindistance to the target position.